Kelangsungan Hidup Ikan Koi (Cyprinus carpio koi) yang Terinfeksi KHV (Koi herpesvirus) [The Survival Of Koi Goldfish (Cyprinus carpio koi) which Infected By KHV (Koi herpesvirus) ] - Ninik Setyorini; Asmaul Khusnah; Lilia Widajatiningrum (Faculty of Fisheries and Marine Universitas Airlangga, 2009)
AbstractThe research aim to know the capability of survival life of the infected KHV koi fish that proved with PCR test. The research held from 2003 until 2008, with the methode took gill sample from the same fish every 4 months. Result of PCR showed positive KHV in each analysis during 4.5 years. According to the PCR test for KHV that conducted for 4.5 years showed that the result always positive in every test.